Kajian Literatur Implementasi Aplikasi Quiz untuk Penilaian Sikap Siswa dalam Pembelajaran PPKn Tingkat SMP - Finatalia, Linda; Sasmita, Wikan (Philosophiamundi, 2025)
Assessment of attitudes is a crucial component in Civic Education (PPKn) learning to develop students’ civic character. However, it is still dominated by conventional methods that are less practical and prone to subjectivity. Meanwhile, technological advancements have introduced digital quiz applications such as Quizizz and Kahoot! which have proven effective in enhancing student engagement and motivation, although their use has predominantly focused on assessing cognitive aspects. This research aims to design an attitude assessment instrument based on digital quiz applications in Civic Education learning at junior high schools, producing a measurement tool that is valid, reliable, practical, and engaging for students. The study employs the Research and Development (R&D) method by Borg and Gall, encompassing stages of needs analysis, instrument development, expert validation, limited trials, revision, and broader field testing. The results of this study are expected to bridge the existing gap in literature regarding the use of digital technology for attitude assessment in Civic Education and provide practical contributions for teachers to implement more objective, efficient, and modern assessments.